The Impact of Teacher’s Empathy on Students' Self-Compassion: An Evidence-Based Intervention Study - Fatima, Noor un Naseeha; Lela, Um I; Khan, Sehrish (Annals of Human and Social Sciences, 2024)
This study aimed to investigate the correlation between a teacher's empathy and a student's self-compassion. It also aimed to enhance empathy in teachers through a pre-stage intervention. The study involved 200 students and 30 teachers, and questionnaires were translated into Urdu for data collection. Statistical Package for Social Sciences (SPSS) was used for data analysis, employing Pearson correlation analysis to assess the relationship between teacher empathy and student self-compassion. Regression analysis was conducted to explore the predictive nature of teacher empathy on student self-compassion. Paired sample t-tests were used to compare pretest and posttest scores. The results indicated a significant positive relationship between teacher empathy and student self-compassion, supporting the hypothesis that empathetic behavior by teachers predicts students' self-compassion. The pre-stage intervention effectively increased empathy in teachers, as reflected by a significant change in scores between the pretest and posttest. These findings highlight the crucial role of teacher empathy in fostering student self-compassion and contribute to the existing literature on the teacher-student relationship, emphasizing the importance of empathy in promoting self-compassion among students.